Cranial anatomy of Paleogene Micromomyidae and implications for early primate evolution. Issue 96 (July 2016) - Bloch, Jonathan I.; Chester, Stephen G.B.; Silcox, Mary T.
Abstract: Paleogene micromomyids are small (∼10–40 g) euarchontan mammals with primate-like molars and postcrania suggestive of committed claw-climbing positional behaviors, similar to those of the extant arboreal treeshrew, Ptilocercus . Based primarily on evidence derived from dental and postcranial morphology, micromomyids have alternately been allied with plesiadapiforms, Dermoptera (colugos), or Primatomorpha (Primates + Dermoptera) within Euarchonta. Partial crania described here of Paleocene Dryomomys szalayi and Eocene Tinimomys graybulliensis from the Clarks Fork Basin of Wyoming are the first known for the family Micromomyidae. The cranium of D. szalayi exhibits a distinct, small groove near the lateral extreme of the promontorium, just medial to the fenestra vestibuli, the size of which suggests that the internal carotid artery was non-functional, as has been inferred for paromomyid and plesiadapid plesiadapiforms, but not for Eocene euprimates, carpolestids, and microsyopids. On the other hand, D. szalayi is similar to fossil euprimates and plesiadapoids in having a bullar morphology consistent with an origin that is at least partially petrosal, unlike that of paromomyids and microsyopids, although this interpretation will always be tentative in fossils that lack exhaustive ontogenetic data. Micromomyids differ from all other known plesiadapiforms in having an inflated cochlear part of the bony labyrinth and a highly pneumatized squamosal and mastoid region with associated septa. Cladistic analyses that include new cranial data, regardless of how bullar composition is coded in plesiadapiforms, fail to support either Primatomorpha or a close relationship between micromomyids and dermopterans, instead suggesting that micromomyids are among the most primitive known primates.